The role of sense of purpose, time management, attendance, sleep and self-esteem in academic performance among university students in Malaysia - Faiz, Masnan; Mohd Juraij, Abd Rani; Nur Salimah, Alias; Miguel Angel, Esquivias; Mohd Shahidan, Shaari; Nanik, Kustiningsih (Elsevier Ltd., 2025)
This research delves into the dynamics influencing the academic performance of undergraduate students in Malaysian universities, specifically examining the role of self-esteem, sense of purpose, time management, sleep quality, and class attendance. With a calculated sample size of 384 obtained from purposive sampling, the study reveals compelling insights. This study aims to determine how students perform in university and what factors contribute the most to their academic performance. The findings underscore the significant influence of self- esteem, sense of purpose, and class attendance on academic performance. These results illuminate the relationship between psychological and behavioral factors in shaping students’ success in the academic sphere. Understanding how these variables relate to academic outcomes provides educators and institutions with valuable information for tailoring support mechanisms and interventions to enhance students’ overall educational experience. In the unique context of Malaysian universities, this research contributes to the broader discourse on factors that contribute to or hinder academic performance among undergraduate students.